Analisis hukum fikih tentang kebolehan dan batasan investasi dalam pengembangan harta - Luhendra, Subhan Karunia Irobi (Maliki Interdisciplinary Journal, 2026)
This study analyses Islamic jurisprudence regarding the permissibility and limitations of investment in asset development using a literature review approach. Investment is understood as a form of asset management aimed at increasing economic value, as long as it remains within the corridor of muamalah principles established by Sharia law. The research method used a literature study by examining primary sources such as the Qur'an, Hadith, and the views of classical and contemporary fiqh scholars regarding economic transactions. The results of the study show that investment is basically permissible in Islam based on the principle of al-ashlu fi al-mu'āmalāt al-ibāhah and the principle of asset development (tathwîr al-mâl). However, this permissibility is limited by a number of Sharia provisions, namely: (1) the prohibition of usury in all its forms; (2) the prohibition of gharar and maysir; (3) the prohibition of investing in sectors that are contrary to Sharia; (4) the obligation of transparency, fairness, and willingness in contracts; and (5) consideration of maslahah and maqāshid sharia in the selection of investment instruments. This study concludes that fiqh provides ample room for investment practices, as long as they comply with sharia provisions that maintain the halal, fairness, and blessing of wealth. These findings provide conceptual guidance for Muslims in determining investment instruments that are in accordance with sharia.